Boyner Group’s Supply Chain Strengthens Women in Business - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
In May 2015, the Boyner Group, in a joint initiative with the International Finance Corporation (IFC), launched the Boyner Group’s good for business program, working with female managers and owners of companies that are suppliers to the Boyner Group. The program is part of Boyner Group’s broader goal of promoting equal opportunity for men and women and establishing gender equality within the company and its supply chain. Women-led companies make up 17 percent of all direct suppliers to the Boyner Group. The program aims to raise their productivity and business performance, building the participants’ capacity through classroom training, coaching, guest lectures, and access to market opportunities through networking events, and a vendor fair. After the successful completion of the pilot phase, the Boyner Group good for business program aims to engage more of its female suppliers through further sessions of the program. The objective of this study is to inspire and inform corporates, donors, and others interested in developing similar programs and to share some of the learning from the pilot phase of the good for business program.